Interannual Variability of Landfast Ice Thickness in the Canadian High Arctic, 1950-89 - Brown, Ross D.; Cote, Phil (ARCTIC, 1992)
A physical one-dimensional heat transfer model of fast ice growth was used to investigate the interannual variability of maximum fast ice thickness at four sites in the High Arctic over the period 1950-89. The insulating role of snow cover was found to be the most important factor, explaining 30-60% of the variance in maximum ice thickness values. Other snow-related processes such as slushing and density variations were estimated to explain a further 15-30% of the variance. In contrast, annual variation in air temperatures explained less than 4% of the variance in maximum ice thickness. No evidence was found for the systematic ice thinning trend anticipated from greenhouse gas-induced global warming. However, recent ice thinning and thickening trends at two sites (Alert and Resolute) are consistent with changes in the average depth of snow covering the ice and may be explained by changes in cyclone frequencies. A response surface sensitivity analysis following Fowler and de Freitas (1900) indicated the High Arctic landfast ice regime would be more sensitive to air temperature variations under a warmer, snowier environment.Key words: landfast ice, snow, interannual variability, climate change, Canadian High Arctic RÉSUMÉ. On s’est servi d’un modèle physique de transfert unidimensionnel de chaleur de la croissance de la banquise côtière pour étudier la variabilité interannuelle de l’épaisseur maximale de la banquise côtière à quatre stations de l’Arctique septentrional au cours de la période allant de 1950 à 1989. Le rôle d’isolant de la couche de neige s’est révélé le facteur le plus important, répondant pour 30 à 60 p. 100 de l’écart observé dans les épaisseurs maximales de glace. On estime qu’une autre partie (15 à 30 p. 100) de l’écart découle d’autres processus liés à la neige, comme la variation de la densité et la gadoue. En revanche, la variation annuelle des températures de l’air est intervenue pour moins de 4 p. 100 de l’écart observé dans les épaisseurs maximales de la glace. On n’a relevé aucune ...